Local practice, translocal people: conflicting identities in the multilingual classroom. (4th March 2017) - Sharples, Robert
ABSTRACT: Increasing rates of migration to the global West are focusing attention on the experiences of young migrants in schools. Too often, these young people are identified in terms of linguistic deficiency but this obscures the skills, experiences and expectations of formal education that they have developed before or during their migration. This article focuses on one learner, 'George', and shows how he adapts his experience of learning in Ethiopia to his new school in London, UK. The data are drawn from a broader ethnographic study of young migrants in one South London school, using extensive participant observation and interviews to argue that the challenges he faces are more related to differing expectations of schooling than they are to a lack of English-language skills. Theoretically, this paper uses Pennycook's notion of 'local practice' to show how young migrants are constantly adapting (or 'relocalising') their expectations of how schools and teachers should behave to make sense of how they do . It further introduces the notion of 'trajectory' to historicise classroom learning, an analytical approach that places situated, local performances of sameness and difference on a broader migration trajectory.